ChemInform Abstract: Si/Mesoporous Carbon Composite as an Anode Material for Lithium Ion Batteries. Issue 14 (20th March 2013) - Shen, Xueyang; Mu, Daobin; Chen, Shi; Xu, Bin; Wu, Borong; Wu, Feng
Abstract Si/mesoporous carbon composite is prepared from a mixture of SiO2 powder, Mg powder, and mesoporous carbon heated in a tube furnace at 650 °C for 6 h under Ar.